2012
DOI: 10.1080/10511970.2010.493548
|View full text |Cite
|
Sign up to set email alerts
|

The Moore Method and the Constructivist Theory of Learning: Was R. L. Moore a Constructivist?

Abstract: Constructivism is currently a hotly debated topic, with proponents and opponents equally adamant and emotional with respect to their viewpoints. Many misconceptions exist on both sides of the debate, and misuses of terminology and attribution are rampant. Constructivism is a theory of learning, not a particular approach to instruction and not a curriculum. Proponents, the majority of whom are involved in K-12 education, argue that reaching more students with a deeper understanding of mathematics requires an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Constructing meaning as derived from experience (Barrett & Long, 2012;Mishra, 2014) was evident in school blogs and reinforced during interviews. School leaders commented on pace and structure of the day noting the discomfort of extended sitting, restricted movement, challenges of transition, and lack of snacks and drinks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing meaning as derived from experience (Barrett & Long, 2012;Mishra, 2014) was evident in school blogs and reinforced during interviews. School leaders commented on pace and structure of the day noting the discomfort of extended sitting, restricted movement, challenges of transition, and lack of snacks and drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Zygmuntís (2016) research study reinforced the importance of sharing experiences and information through discourse leading to a rise in consciousness and understanding within a bounded culture. Along with social cultural theory is the concept of constructivism where meaning is constructed through an experience (Barrett & Long, 2012;Mishra, 2014). El-Deghaidyís (2012) study focused on the importance of constructivism from the perspective of teachersí as researchers; however, the findings can be applied to school leaders who take an active role in constructing knowledge through personal experiences within the school culture.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Constructivist learning theory is the key theoretical lens utilized in this study to explain the findings. Constructivism is a theory of learning, not a method of instruction or a curriculum (Barrett & Long, 2012). The view of constructivism as a learning theory has guided most of the development of constructivist pedagogy (Richardson, 2003(Richardson, , p. 1624.…”
Section: Constructivist Theory Of Learningmentioning
confidence: 99%
“…This theory applies to this study in that the students with hearing impairment are identified, assessed and placed in special schools for the deaf so that their academic needs are met. An IEP is to be developed by the teachers who are the curriculum implementers by finding out the learner's strengths and weaknesses and then coming up with short-term and long-term objectives with specified evaluation procedures (Barrett & Long, 2012). Teachers play a major role in education for the deaf since they should have adequate training, a positive attitude, good communication skills with learners with deafness and appropriate pedagogical practices that will enable them to provide individualized curricular instructions that yield good academic results.…”
Section: Theoretical Reviewmentioning
confidence: 99%